Brucein D, a Naturally Occurring Tetracyclic Triterpene Quassinoid, Induces Apoptosis in Pancreatic Cancer through ROS-Associated PI3K/Akt Signaling Pathway - Lai, Zheng-Quan; Ip, Siu-Po; Liao, Hui-Jun; Lu, Zheng; Xie, Jian-Hui; Su, Zi-Ren; Chen, Yun-Long; Xian, Yan-Fang; Leung, Po-Sing; Lin, Zhi-Xiu (Frontiers in Pharmacology, 2017)
Brucein D (BD), a major active quassinoid in Brucea javanica, has exhibited pronounced anticancer activities. However, the biologic mechanisms have not been fully explored. In this study, BD exhibited more potent cytotoxic effect on pancreatic cancer (PanCa) cell lines, while exerted weaker cytotoxic effects on GES-1 cells (non-tumorigenic). BD was shown to elicit apoptosis through inducing both the intrinsic and extrinsic mitochondria-mediated caspase activations. Furthermore, the BD-induced apoptotic effects were dependent on the accumulated reactive oxygen species (ROS) and inactivation of PI3K/Akt signaling pathway. Pretreatment with tempol completely prevented the cellular apoptosis induced by BD, and recovered the inactivation of AKT, which suggested ROS essentially involved in BD-elicited apoptosis and down-regulation of PI3K/Akt pathway. In addition, the results obtained from orthotopic xenograft in nude mice were congruent with those of the in vitro investigations. These results support the notion that BD held good potential to be further developed into an effective pharmaceutical agent for the treatment of PanCa.